2004
DOI: 10.1203/01.pdr.0000128978.90201.1d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Short- and Long-Duration Oxygen Treatment after Cerebral Asphyxia in Newborn Piglets

Abstract: We tested whether reoxygenation with 100% O(2) for 5 min after experimental asphyxia in newborn piglets was as efficient as 100% O(2) for 20 min compared with room air. Forty-one anesthetized piglets, 1-3 d old, were randomized to cerebral hypoxemia-ischemia-hypercapnia (HIH) or control (n = 5). HIH was achieved by ventilation with 8% O(2), temporary occlusion of the common carotid arteries, and adding of CO(2). After 25 min, reoxygenation-reperfusion was started with 100% O(2) for 20 min (group 1, n = 12), 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…Similarly, in other studies, the duration of postischemic reoxygenation with use of pure oxygen varies from 5 min to 24 h regardless of the resuscitation-induced changes in CBF (4,5,25). This may limit the clinical value of experimental data.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, in other studies, the duration of postischemic reoxygenation with use of pure oxygen varies from 5 min to 24 h regardless of the resuscitation-induced changes in CBF (4,5,25). This may limit the clinical value of experimental data.…”
mentioning
confidence: 95%
“…To date, results of these studies are conflicting. For instance, it was reported that in asphyxiated pigs the Re-O 2 restored CBF significantly faster and more complete compared with Re-Air (4). Significantly higher levels of excitatory amino acids were found in the striatum of newborn HI-piglets Re-Air compared with Re-O 2 piglets which may be indicative of less favorable neurologic prognosis for Re-Air animals (5).…”
mentioning
confidence: 99%
“…Research in animal (Herpin et al, 2001;MotaRojas et al, 2005a,b;2006a,b) and human perinatology (Randall et al, 1979;Tollofsrud et al, 2001;Solas et al, 2004) have used sows' foetuses and newborns as experimental animal models (Gonzalez-Lozano et al, 2009a,b;Olmos-Hernandez et al, 2008), because this species has shown similarities to human medicine in terms of changes in energy metabolism during normal and pathological childbirth. Foetal growth is a complex process that involves the interaction of mother, placenta and foetus.…”
Section: Introductionmentioning
confidence: 99%
“…Australia, Canada, Finland, the Netherlands, Sweden, and the United Kingdom recommend initial ventilation with air, because of the results from several experimental (2)(3)(4)(5) and clinical (6 -13) studies indicating that resuscitation with 100% oxygen is harmful. In the clinical studies, the time of exposure to 100% oxygen was typically 5-7 min (8,13), whereas only one animal study (5) has investigated an exposure time to oxygen less than 15 min.…”
mentioning
confidence: 99%